Prevalence of individual and bulk tank milk antibodies of bovine herpesvirus type 1 and its relation to milk quality parameters on dairy farms in Catalonia (north‐east Spain). Issue 1 (22nd June 2017) - Armengol, Ramon; Villalba, Daniel; Coma, Ester; Porquet, Lourdes; Jubert, Anna; Nogareda, Carmina
Abstract : Bovine herpesvirus type 1 (BoHV‐1) is the causative agent for infectious bovine rhinotracheitis and infectious pustular vulvovaginitis in cows or balanoposthitis in bulls. In this study, individual and bulk tank milk (BTM) samples from 5 Catalan dairy farms with different control strategies against BoHV‐1 were analysed during the course of a year for milk quality parameters and glycoprotein E ( gE) antibodies. Detection of gE antibodies was carried out with ELISA techniques. Prevalence of BoHV‐1 varied between farms, and was stable during the study in individual and BTM samples. Comparing the antibody results of samples with milk quality parameters, positive samples with higher levels of antibodies corresponded to lower lactose and to higher percentages of fat and somatic cells.